Extraordinary luminous soft x-ray transient maxi j0158-744 as an ignition of a nova on a very massive o-ne white dwarf - Morii, M.; Tomida, H.; Kimura, M.; Suwa, F.; Negoro, H.; Serino, M.; Kennea, J.; Curran, Peter; Walter, F.; Kuin, N.; Pritchard, T.; Nakahira, S.; et al. (Institute of Physics Publishing, 2013)
We present the observation of an extraordinary luminous soft X-ray transient, MAXI J0158-744, by the Monitor of All-sky X-ray Image (MAXI) on 2011 November 11. This transient is characterized by a soft X-ray spectrum, a short duration (1.3 × 103 s < Td < 1.10 × 104 s), a very rapid rise (< 5.5 × 103 s), and a huge peak luminosity of 2×1040 erg s-1 in 0.7-7.0 keV band. With Swift observations and optical spectroscopy from the Small and Moderate Aperture Research Telescope System (SMARTS), we confirmed that the transient is a nova explosion, on a white dwarf in a binary with a Be star, located near the Small Magellanic Cloud. An extremely early turn-on of the super-soft X-ray source (SSS) phase (< 0.44 d), the short SSS phase duration of about one month, and a 0.92 keV neon emission line found in the third MAXI scan, 1296 s after the first detection, suggest that the explosion involves a small amount of ejecta and is produced on an unusually massive O-Ne white dwarf close to, or possibly over, the Chandrasekhar limit. We propose that the huge luminosity detected with MAXI was due to the fireball phase, a direct manifestation of the ignition of the thermonuclear runaway process in a nova explosion.